Transformation beyond Transgression; Resistance-based System Improvement in Kitab Kuning Reading Acceleration Program - Achmad Muhlis; Moch. Chalid Wardi; Masyithah Mardhatillah; Sri Rizqi Wahyuningrum; Imam Khomaeni Hayatullah (Nazhruna: Jurnal Pendidikan Islam, 2025)
This paper aims to discover how santri’s resistance within kitab kuning reading acceleration program recently popular in Madurese pesantren turns out to improve the program itself. Santris’ resistance becomes a big deal considering its contradiction to ethical unwritten rules in pesantren while the fact shows how this phenomenon strikes. For that purpose, genealogy of such programs is firstly identified along with characteristics of each to figure out how, beyond the existing diversities, the programs share the same pattern, including the common root and impact of resistance. Involving 240 informants from santri, ustad, and program providers, this mixed research expanded its data compilation with in-depth interviews engaging some selected informants as well as comprehensive desk review. The result discloses  pesantren networking in intellectual hub responding to nowadays challenges in the decrease of kitab kuning reading proficiency along with dynamics of resistance among santri, mainly in negotiation type through emotional, verbal, and physical expression. Despite the fact that resistance mutates along with punishment as a part of rule, it has less influence on the program accomplishment, implying how both program and its resistance based system improvement transform the way Islamic education takes place beyond the studens’ sort of transgression.